Penataan Kawasan Wisata Pantai Berbasis Komunitas Nelayan di Pantai Bintang Kabupaten Lombok Utara - Pascaghana Jayatri; Zaedar Gazalba, ST., MT.; Giska Ayu Pradana Putri Kamase, ST.; Fauza Hastati, ST., MT.; Aldhi Nugraha Anantama, S. Arch., M.Arch. (Jurnal Anala, 2023)
The arrangement of coastal areas as tourist attractions in Medana Village, Tanjung subdistrict, North Lombok Regency has been massively developed in line with the economic revival of North Lombok after the devastating earthquake in 2018 and Covid-19 in 2020. Bintang Beach is one of the tourist destinations. Local mainstays along the Medane coastal area with infrastructure built in 2016 were also affected by the earthquake, it is necessary to reorganize the area so that it becomes vital again and can be integrated with the coastal area to the north and fishermen's settlements to the south. The problems studied in this research are direction and concept of structuring coastal areas based on fishing communities, as well as the design of structuring models that can be applied as a basic reference for restructuring areas in future development. The method used is Qualitative Descriptive with primary data collection techniques using direct site surveys, and secondary data in the form of related policy references. Analysis is carried out by exploring the potential of the area through a tourism component approach, and SWOT analysis to project facility needs and tourism sustainability strategies. The concept results obtained were 8 regional planning concepts. The model design a regional master plan with a fishing community-based approach.